(untitled) - Wells, Dare A. (New York, 1967)
The Lagrangian method of dynamics is applicable to a very extensive field of particle and rigid body problems, ranging from the simplest to those of great complexity. The advantages of this procedure over conventional methods are, for reasons which follow, of outstanding importance.
Keywords: Dynamics,Động lực học